THE INFLUENCE OF PUBLIC SERVICE QUALITY ON PUBLIC SATISFACTION AT THE PEDAMAI VILLAGE OFFICE, STABAT DISTRICT, LANGKAT REGENCY - Nur Zahra Ningtias Girsang; Cut Sukmawati; Bobby Rahman; Murniati; Risna Dewi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The quality of public services is a key indicator in assessing the effectiveness of government. Good service can increase public trust in the government and have a positive impact on social stability. Quality public services not only meet the needs of the community but also reflect the government's commitment to creating prosperity. One important element in public administration is the quality of service, namely quality services that include timely, fair, transparent, easily accessible, provided politely and friendly with predetermined standards. At the Perdamaian Village Office, Stabat District, Langkat Regency, there are still several public complaints regarding the speed of service, service procedures, which indicate the need to improve service quality. This condition has the potential to affect public satisfaction. This study aims to analyze the effect of public service quality on public satisfaction at the Perdamaian Village Office, Stabat District, Langkat Regency. The research method used is a quantitative approach with data collection techniques through questionnaires to 100 respondents determined using the Slovin formula. Data analysis using simple linear regression showed a significance value of 0.000 (<0.05) with a coefficient of determination (R2 ) of 0.607. The results of the study show that the quality of public services has a significant influence on public satisfaction by 60.7%, while 39.3% is influenced by other factors outside this study such as employee performance, infrastructure, service policies, and management systems.